Subdivision Or Refinement B-Spline Curves And Surfaces - Kang , Yun Pyng (2005)
CAGD is the abbreviation for Computer Aided Geometric Design. In CAGD, the subdivision scheme is gaining popularity among the computer graphics and geometric modeling community and has achieved considerable success. CAGD ialah singkatan bagi " Computer Aided Geometric Design" atau da~am bahasa Malaysia sebagai " Rekabentuk Geometri Berbantukan Komputer " . Dalam CAGD, kaedah subbahagian semakin terkenal di kalangan komuniti komputer grafik dan pemodelan geometri.